Statistical Analysis of Effect of pH Treatment on Biohydrogen Production from POME Waste - Junita Tarigan; Armansyah Halomoan Tambunan; Radite Praeko Agus Setiawan; Obie Farobie; Furqon (PERTETA, 2022)
Palm Oil Mill Effluent (POME) has the potency to be converted to biohydrogen by dark fermentation. The statistical approach was used to determine the relationship between pH and biohydrogen production. This study aims to investigate the effect of pH on biohydrogen production with a statistical approach. Three substrates were treated with neutral pH and three without pH treatment. This experiment used the trapezoidal numerical integration method to get the total production of H2 produced per measurement time interval. There are nine substrate combinations tested. Three tests concluded that there was no difference in hydrogen production due to the pH treatment, and the sixth test concluded that there was a difference in hydrogen production due to the influence of pH. The tendency of every substrate to influence biohydrogen production without pH treatment and with pH treatment is a polynomial degree 3.